Association of anaemia, co-morbidities and red blood cell transfusion according to age groups: multicentre sub-analysis of the German Patient Blood Management Network Registry. Issue 6 (3rd November 2022) - Blum, Lea Valeska; Schmitt, Elke; Choorapoikayil, Suma; Baumhove, Olaf; Bayer, Alexandra; Friederich, Patrick; Friedrich, Jens; Geisen, Christof; Gruenewald, Matthias; Gutjahr, Martin; Herrmann, Eva; Müller, Markus; et al.
Abstract: Background: Blood transfusions are common medical procedures and every age group requires detailed insights and treatment bundles. The aim of this study was to examine the association of anaemia, co-morbidities, complications, in-hospital mortality, and transfusion according to age groups to identify patient groups who are particularly at risk when undergoing surgery. Methods: Data from 21 Hospitals of the Patient Blood Management Network Registry were analysed. Patients were divided into age subgroups. The incidence of preoperative anaemia, co-morbidities, surgical disciplines, hospital length of stay, complications, in-hospital mortality rate, and transfusions were analysed by descriptive and multivariate regression analysis. Results: A total of 1 117 919 patients aged 18–108 years were included. With increasing age, the number of co-morbidities and incidence of preoperative anaemia increased. Complications, hospital length of stay, and in-hospital mortality increased with age and were higher in patients with preoperative anaemia. The mean number of transfused red blood cells (RBCs) peaked, whereas the transfusion rate increased continuously. Multivariate regression analysis showed that increasing age, co-morbidities, and preoperative anaemia were independent risk factors for complications, longer hospital length of stay, in-hospital mortality, and the need for RBC transfusion. Conclusion: Increasing age, co-morbidities, and preoperative anaemia are independent risk factors for complications, longer hospital length of stay, in-hospital mortality, and the need for RBC transfusion. Anaemia diagnosis and treatment should be established in all patients. Abstract : The association between age, preoperative anaemia, and co-morbidities on perioperative outcome in surgical patients, was performed to augment our knowledge on each age decade. This big data set, including 1 117 919 patients aged 18–108 years, gives detailed information and can be used to plan prospective studies in the setting of surgical intervention, age, complications, and transfusion management. To conclude, increasing age, preoperative anaemia and the sum of co-morbidities have been proven to be independent risk factors for complications, mortality, length of in-hospital stay, and the need for blood products.